Sprawozdanie z międzynarodowego seminarium naukowego: EGALS seminar 2017 – Future of Animal Law in Europe, Katowice, 27 września 2017 - Kowalska, Aleksandra (Zoophilologica. Polish Journal of Animal Studies, 2018)
Aleksandra Kowalska's report on the EGALS seminar titled "Future of Animal Law in Europe" organized in Katowice on September 27th, 2017.